Spolupráce při správě majetku řeholního institutu na území místní církve - Menke, Monika (Prawo Kanoniczne, 2020)
Recent documents of the Apostolic See more strongly reflect the importance of responsible property management in religious institutes, the supervision and transparency of such administration and even incorporated its importance in the field of religious formation. The article recapitulates the position of religious institutes within the local church, their cooperation in the area of property management and finally also concrete steps in the management of religious institutes in the Czech Republic after the first few years of implementation of Act No. 428/2012 Coll., on proeprty settlement with churches and religious societies. The law includes physical restitution in kind with financial compensation. Religious institutes partially deposit and partially invest money from financial compensation for unreleased property. The aim of these steps in the future should be the economic separation of churches (including religious orders) from the state, which enable financial self-sufficiency of churches.